Maternal and Perinatal Outcome of Perimortem Caesarean Section - Fizza Ali Khan, Rabia Jamil, Sofia Butt, Syed Farjad Sultan, Safia Zafar, Tayyeba Anbreen (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To describe characteristics, etiological factors, maternal and perinatal outcome of perimortem Caesarean section. Design: Prospective study Setting: Emergency Room of Department of Obstetrics & Gynecology Unit IDr.Ruth KM Pfau Civil Hospital & Dow Medical College, Karachi. Methodology: This study was carried out in the Department of Obstetrics and Gynaecology, Civil Hospital Karachi from November 2020 to March 2021. All women who were presented in emergency in a collapsed state were included in the study and those women who were brought dead were excluded. Clinical details including age, gestational age, reason for perimortem Caesarean section, perinatal and maternal outcome were recorded on a predesigned proforma. Results: A total of 27 women underwent perimortem Cesarean section. The mean age of women who underwent PMCS was 26±6.5 years, and mean gestational age was 35±4weeks. Sixteen (59%) women were referred from either primary care or small clinics. Majority 15(55%), underwent PMCS within 5 minutes of maternal collapse and 12(44%) underwent PMCS, after 5 minutes of collapse. Septic shock 21(77%) was the main etiological factor for PMCS, followed by hypertension and cardiomyopathy 2(7%) each. Twenty three (85%) women survived, following PMCS, whereas 4(14%) died. Reasons for maternal death included hepatic encephalopathy(1), peripartum cardiomyopathy(2), eclampsia(1). The perinatal mortality was high, with only 14(51%) live birth and mean APGAR score at 1 and 5 minutes was 3. The mean stay in intensive care was 37± 35 hours, whereas mean stay in ward was 57±39 hours. Practical implications: This study suggests that if perimortem caesarean section accomplished in a timely manner, it can improve fetomaternal outcome. Conclusion: Perimortem Caesarean section can improve upon maternal survival. Greater awareness among doctors, multidisciplinary approach, proper documentation and information for family members are cornerstone of this emergency procedure. Keywords: Perimortem Cesarean section, septic shock,eclampsia,postpartumhaemorrhage, maternal mortality.